Rooted - Wildschut, Henk 1967- (Henk Wilschut, 2019)
Rooted is the third and last part of an unintended trilogy on the lives of refugees and migrants. The three books were not conceived as a series sharing a preconceived structure or format, but are at most loosely related in content, photography and book design. The books Shelter and Ville de Calais arose independently, each telling a distinct story in its own narrative style and logic. Rooted returns to a phenomenon that was already noted in Ville de Calais: the many refugee camp residents who find hope, consolation and dignity in nurturing a few plants. These miniature gardens are often little more than a few tin cans planted with flowers, or of a handful of seeds or bulbs struggling to sprout in a patch of meagre soil. Some residents will go so far as to hammer in a few stakes or construct a makeshift fence to mark off a temporary claim to a bit of territory. The phenomenon is not of course limited to Calais, for almost anyone who has been expelled from their homeland will eventually reconcile themselves to the unfamiliar ground where they have ended up. To me, the herbs, flowers and miniature gardens that they plant symbolize a longing for something resembling a normal existence.--https://rooted.nu/ (viewed 10/14/2019)
Keywords: Wildschut, Henk -- 1967-; Flüchtlingslager; Pflanzen -- Motiv; Fotografie; Refugee camps / France / Calais / Pictorial works; Refugee camps / Jordan / Pictorial works; Refugee camps / Lebanon / Pictorial works; Refugee camps / Tunisia / Pictorial works; Plants / Middle East / Pictorial works; Plants / Africa, North / Pictorial works; Plants / Europe / Pictorial works; Documentary photography / 21st century; Photography, Artistic / 21st century; Refugees; Immigrants; Bildband